Parental visiting, communication, and participation in ethical decisions: a comparison of neonatal unit policies in Europe. Issue 2 (1st September 1999) - Cuttini, M; Rebagliato, M; Bortoli, P; Hansen, G; de Leeuw, R; Lenoir, S; Persson, J; Reid, M; Schroell, M; de Vonderweid, U; Kaminski, M; Lenard, H; et al.
Abstract : AIM: To compare neonatal intensive care unit policies towards parents' visiting, information, and participation in ethical decisions across eight European countries. METHODS: One hundred and twenty three units, selected by random or exhaustive sampling, were recruited, with an overall response rate of 87%. RESULTS: Proportions of units allowing unrestricted parental visiting ranged from 11% in Spain to 100% in Great Britain, Luxembourg and Sweden, and those explicitly involving parents in decisions from 19% in Italy to 89% in Great Britain. Policies concerning information also varied. CONCLUSIONS: These variations cannot be explained by differences in unit characteristics, such as level, size, and availability of resources. As the importance of parental participation in the care of their babies is increasingly being recognised, these findings have implications for neonatal intensive care organisation and policy.